2018
DOI: 10.1101/482653
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Connectomic identification and three-dimensional color tuning of S-OFF midget ganglion cells in the primate retina

Abstract: The first step of color processing in the visual pathway of primates occurs when signals from short-(S), middle-(M) and long-(L) wavelength sensitive cone types interact antagonistically within the retinal circuitry to create color-opponent pathways. The midget (L vs. M or 'red-green') and small bistratified (S vs. L+M, or 'blue-yellow') appear to provide the physiological origin of the cardinal axes of human color vision. Here we confirm the presence of an additional S-OFF midget circuit in the macaque monk… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 82 publications
(115 reference statements)
0
2
0
Order By: Relevance
“…Beyond central retina, the impact of mixing S, L, and M cone inputs on the spectral tuning of S OFF midget cells is less clear, but it would predict that these cells might show sensitivity that does not lie strictly along the S versus LϩM cardinal axis (FIGURE 10D). In a recent study designed to test this idea directly, OFF midget ganglion cells were recorded in the near retinal periphery, and chromatic stimuli were modulated around a color circle in LϩM versus S cone opponent space (506). The results showed that all ON midget cells and the majority of OFF midgets lacked a measurable S cone input.…”
Section: S Off Midget Ganglion Cellmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond central retina, the impact of mixing S, L, and M cone inputs on the spectral tuning of S OFF midget cells is less clear, but it would predict that these cells might show sensitivity that does not lie strictly along the S versus LϩM cardinal axis (FIGURE 10D). In a recent study designed to test this idea directly, OFF midget ganglion cells were recorded in the near retinal periphery, and chromatic stimuli were modulated around a color circle in LϩM versus S cone opponent space (506). The results showed that all ON midget cells and the majority of OFF midgets lacked a measurable S cone input.…”
Section: S Off Midget Ganglion Cellmentioning
confidence: 99%
“…Over 50 years ago, action potential recordings from neurons in the parvocellular layers of the LGN by Hubel and Wiesel presented a tantalizingly simple picture of how a single visual pathway might be the neural basis for "opponent color theory" (498), the dominant idea in color science at that time. Today we are confronted with a dizzyingly complex array of pathways and mechanisms that play varied roles in color processing at the retinal level; indeed, new circuitries that may be fundamental to understanding human color vision are still being discovered (506). The motivation for this review is to consider our current understanding of the cell types and circuits of the retina across vertebrate species, from teleost fish like the zebrafish and goldfish, to intensively studied mammals like mouse and rabbit, and to human and non-human primates where certain aspects of color circuitry appear to have been reinvented during primate evolution.…”
Section: Introductionmentioning
confidence: 99%